Saliva as an alternative biological fluid for therapeutic drug monitoring of mycophenolic acid in renal transplant recipients - Kundalić, Ana; Stefanović, Nikola; Živanović, Slavoljub; Veličković-Radovanović, Radmila; Catić-Djordjević, Aleksandra (Archives of Pharmacy, 2022)
Mycophenolic acid (MPA) is widely used to prevent graft rejection in renal transplant recipients. For MPA therapeutic drug monitoring (TDM), saliva has been investigated as an alternative fluid to plasma. The main advantages of saliva are the non-invasive and cost-effective sample collection, permitting more frequent sampling. The purpose of this study was to examine the correlation between plasma and saliva MPA concentrations in renal transplant recipients and the potential of saliva for TDM of MPA. All patients (average age 44.33±11.45 years) were receiving 720-1440 mg/day of MPA (as enteric-coated mycophenolate sodium). Twenty-three paired blood and saliva samples were collected at pre-dose for MPA plasma and saliva trough concentration (C0) measurement. Both samples were centrifuged at 3000 rpm for 15 min and kept at -80°C until analysis. The MPA plasma C0 concentrations were determined by the validated high-performance liquid chromatography (HPLC) method. The liquid chromatography coupled to mass spectrometry (LC-MS) method was developed for determining MPA in saliva. Mean ± SD of MPA plasma C0 concentrations (5.24±2.19 µg/mL) in renal transplant recipients was about 100-fold higher than in saliva (55.53±24.75 ng/mL), which could be explained by the fact that the total fraction was analyzed in the plasma, and only the free fraction was assessed in saliva. The average salivary MPA C0 concentration correlated well with its plasma concentration (r=0.8474). Based on the good correlation between salivary and plasma MPA concentration, saliva can be considered as an alternative to plasma, particularly for unbound MPA monitoring in renal transplant recipients.